2007
DOI: 10.2475/01.2007.05
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp U-Pb evidence for a Late Silurian age of metasedimentary rocks in the Merrimack and Putnam-Nashoba terranes, eastern New England

Abstract: Zircon and monazite were extracted from ϳ5 to 10 kg rock samples by routine mineral separation processes, including crushing, pulverizing, Wilfley table concentration of heavy minerals, and purification of mineral fractions using magnetic separation and methylene iodide. Detrital zircons were sprinkled onto double-stick tape to obtain relatively unbiased samples. Individual grains of monazite and titanite were handpicked under a binocular microscope. All samples were mounted in epoxy, ground to nearly half-thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 66 publications
0
25
1
Order By: Relevance
“…The earliest sediments deposited in the Central Maine Basin were derived from Laurentia whereas the uppermost formations preserve paleocurrent indicators from the east, suggesting an outboard source thought to be Avalonia Hanson et al 1993;Bradley and Hanson 2002). Because sediments carry the major and trace element, isotopic, and detrital zircon signatures of their source rocks (O'Nions et al 1983;Allegre and Rousseau 1984;Michard et al 1985;McLennan et al 1990;Gleason et al 1994;Anderson and Sampson 1995;Bock et al 1998;Wintsch et al 2007), we undertook this study to determine whether or not the bulk-rock geochemical characteristics and detrital zircon geochronology of easterly derived sediments, i.e., the Carrabassett Formation of Maine, would identify the outboard terrane that collided with Laurentia. We compare these geochemical and geochronological parameters with those of the older formations of the Central Maine Basin in order to make comparisons between the source regions of sediments shed from Laurentia and outboard sources.…”
Section: Fig 1 Generalized Geologic Map Showing the Locations Of Thmentioning
confidence: 99%
See 3 more Smart Citations
“…The earliest sediments deposited in the Central Maine Basin were derived from Laurentia whereas the uppermost formations preserve paleocurrent indicators from the east, suggesting an outboard source thought to be Avalonia Hanson et al 1993;Bradley and Hanson 2002). Because sediments carry the major and trace element, isotopic, and detrital zircon signatures of their source rocks (O'Nions et al 1983;Allegre and Rousseau 1984;Michard et al 1985;McLennan et al 1990;Gleason et al 1994;Anderson and Sampson 1995;Bock et al 1998;Wintsch et al 2007), we undertook this study to determine whether or not the bulk-rock geochemical characteristics and detrital zircon geochronology of easterly derived sediments, i.e., the Carrabassett Formation of Maine, would identify the outboard terrane that collided with Laurentia. We compare these geochemical and geochronological parameters with those of the older formations of the Central Maine Basin in order to make comparisons between the source regions of sediments shed from Laurentia and outboard sources.…”
Section: Fig 1 Generalized Geologic Map Showing the Locations Of Thmentioning
confidence: 99%
“…It was originally defined by Katz (1917) to consist of the Kittery, Eliot, and Berwick formations that constitute a thick sequence of calcareous turbidites in the New Hampshire and Maine (Katz 1917;Billings 1956;Bothner et al 1984;Bothner and Hussey 1999). Recently, Wintsch et al (2007) concluded from detrital zircon geochronology that the Berwick Formation was Silurian and Laurentia-derived, whereas the Kittery Formation (middle Ordovician or younger), with its paleocurrent indicators of an eastern source and different detrital zircon signatures, is peri-Gondwanan. They interpreted the fault that separates the Berwick Formation from the Kittery and Eliot formations as a thrust fault that placed the Laurentiaderived Berwick on top of the peri-Gondwana-derived Kittery and Eliot.…”
Section: Merrimack Troughmentioning
confidence: 99%
See 2 more Smart Citations
“…New England is composed of tectonic blocks, microcontinents, and/or terranes accreted to eastern Laurentia primarily during the Silurian-Devonian Salinic, Acadian, and Neoacadian orogenies, and the PennsylvanianPermian Alleghanian orogeny (O'Hara and Gromet 1985;Goldstein 1989;Skehan and Rast 1990;Wintsch et al 1992Wintsch et al , 2007Rast and Skehan 1993;Hepburn et al 1995;van Staal 2005;Hibbard et al 2006Hibbard et al , 2007. Over the last three decades, the number and extent of these terranes and the timing of their accretion and juxtaposition have been debated.…”
Section: Introductionmentioning
confidence: 99%